2015 53rd Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2015
DOI: 10.1109/allerton.2015.7447017
|View full text |Cite
|
Sign up to set email alerts
|

Improving MIMO detection performance in presence of phase noise using norm difference criterion

Abstract: Practical MIMO communication systems suffer performance loss from oscillator phase noise. In particular, if maximum likelihood (ML) detection is performed naively without considering the phase noise, it results in an error floor in its symbol error probability. In this paper, we propose a method to detect the correctness of the naive ML solution in the presence of strong phase noise. A criteria based on the ML cost differences between the ML solution and the actually transmitted vector is used to determine a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Data detection in large scale MIMO systems using successive interference cancellation (SIC) is given in [28]. MIMO data detection in the presence of phase noise is given in [29]. Detection of LDPC coded symbols in MIMO systems is discussed in [30].…”
Section: Introductionmentioning
confidence: 99%
“…Data detection in large scale MIMO systems using successive interference cancellation (SIC) is given in [28]. MIMO data detection in the presence of phase noise is given in [29]. Detection of LDPC coded symbols in MIMO systems is discussed in [30].…”
Section: Introductionmentioning
confidence: 99%
“…Proposition 1. Let A A A and b b b be defined as in (12). Then we have the following approximation of the log-likelihood function ln…”
Section: A Proposed Approximation Of the Likelihood Functionmentioning
confidence: 99%
“…Related Work. Receiver design with phase noise mitigation has been extensively investigated in the past years (see [11], [12] and references therein). More complex channel models, including multi-carrier systems (e.g., OFDM) and time-correlated phase noises (e.g., the Wiener process) have also been considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 × 2 MIMO phase noise channel with independent transmit and receive phase noises at each antenna was studied in [12], where the authors showed that the multiplexing gain is 1 2 for a specific class of input distributions. For general MIMO channels with separate phase noises, estimation and detection algorithms have been proposed in [13], [14]. However for such channels, even the multiplexing gain is unknown, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%